2017
DOI: 10.1111/aogs.13260
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evaluation of painful symptoms and fertility after surgery for large rectovaginal endometriosis nodule: a retrospective study

Abstract: Our study demonstrates that rectal shaving, when feasible for rectovaginal nodule (>2 cm) infiltrating the digestive serosa, has equal impact on pain and pregnancy rates compared with colorectal resection at long-term follow-up, with low complication and favorable pregnancy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
0
14
1
Order By: Relevance
“…Furthermore, we did not observe significant differences in long‐term functional outcomes regarding minor or major LARS nor a high rate of bowel stenosis in SR patients (1.2%) as reported by Roman et al, in their randomized controlled trial comparing SR and DR reaching 15.2% . Therefore, we do not strictly support the tendency to promote conservative surgical techniques wherever and whenever possible and even in large lesions as suggested by Donnez et al, Bordel and colleagues or Nezhat et al. Furthermore, our rate of protective ileostomies with 11.8% in the SR group and 0% in the DR is much lower than those reported by groups strongly supporting conservative surgery .…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, we did not observe significant differences in long‐term functional outcomes regarding minor or major LARS nor a high rate of bowel stenosis in SR patients (1.2%) as reported by Roman et al, in their randomized controlled trial comparing SR and DR reaching 15.2% . Therefore, we do not strictly support the tendency to promote conservative surgical techniques wherever and whenever possible and even in large lesions as suggested by Donnez et al, Bordel and colleagues or Nezhat et al. Furthermore, our rate of protective ileostomies with 11.8% in the SR group and 0% in the DR is much lower than those reported by groups strongly supporting conservative surgery .…”
Section: Discussioncontrasting
confidence: 66%
“…Standard colorectal resection, which is primarily performed for cancer of the rectum or sigmoid colon, involves mobilization of the rectosigmoid as in standard total mesorectal excision surgery including resection of a significant length of the bowel around the lesion as well as the surrounding tissue up to the plane between the mesorectum and the presacral fascia . This standard technique may also be applied for colorectal DIE in institutions where the general surgeon is primarily involved for segmental resections as reported previously . In accordance with previous publications, our strategy for surgical resection of bowel disease includes conservative and radical, ie, segmental removal of DIE with the aim of limiting the resected segment to the area of infiltration with a tubular, nerve‐sparing, but also mesorectum and artery‐sparing, treatment approach.…”
Section: Introductionmentioning
confidence: 73%
“…When considering all included studies (n = 41) [11,20−59], no significant difference in overall recurrence was found among the 3 surgical groups, with ORs of 1.47 (95% CI, 0.89−2.43; I 2 = 72%; p = .7) ( Fig. 2A) [21,22,24,25,27,30,47,53], 1.08 (95% CI, 0.59−1.98; I 2 = 0%; p = .95) ( Fig. 2B) [21,25,35,40,47,53,59], and 1.21 (95% CI, 0.62−2.35; I 2 =57%; p = .58) ( Fig.…”
Section: Overall Recurrencementioning
confidence: 99%
“…The time to recurrence was highly variable, depending on when the recurrence was considered to have occurred. Ten studies mentioned details of the interval up to recurrence (Table 3) [11,20,22,31,33,38,39,42,46,51]: five reported the time between the index surgery and follow-up surgery [22,33,39,42,46], and the remaining 5 reported the time between the index surgery and recurrence of clinical symptoms or imaging evidence of endometriosis [11,20,31,38,51]. In the former case, the time to recurrence ranged between 14 [39] and 90 [33] months and in the latter between 12 [20] and 94 months [22].…”
Section: Time To Recurrencementioning
confidence: 99%
“…Eventually, 17 articles [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] were included in our study,1wasRCT,7 were prospective cohort studies and the others were retrospective. At the beginning, 153 studies were found in PUBMED 163 studies in MEDLINE and 227 studies in Cocharane Library.…”
Section: Resultsmentioning
confidence: 99%